Low-cost, high-resolution method for determining cruise ship anchoring behaviour to assess potential impacts on sensitive tropical marine habitats - Small, Micaela; Oxenford, Hazel A. (Frontiers in Conservation Science, 2025)
Anchoring is well known to cause potentially significant damage to sensitive marine habitats, yet is relatively poorly studied, especially for cruise ships. These are among the largest ships in the world and frequently seek to visit relatively unspoilt tropical destinations, where docking facilities are absent or inadequate, resulting in cruise ships anchoring instead. Limited resources in agencies tasked with marine management in these destinations often constrain the ability to assess potential impacts and develop robust anchoring protocols based on scientific information that seek to preserve valuable marine habitats. In this study we present a low-cost method for identifying anchoring events and studying the detailed movement of cruise ships at anchor to determine their anchoring footprint and to map maximum potential habitat damage. This methodological approach using open access automatic identification systems (AIS) data is particularly well suited to destinations where resources for marine management are scarce, yet the environmental and socioeconomic cost of anchoring damage is likely to be high.